BLACK MALE EXCEPTIONALISM?. (3rd January 2014) - Butler, Paul
Abstract "Black male exceptionalism" is the premise that African American men fare more poorly than any other group in the United States. The discourse of Black male exceptionalism presents African American men as an "endangered species." Some government agencies, foundations, and activists have responded by creating "Black male achievement" programs. There are almost no corresponding "Black female achievement" programs. Yet empirical data does not support the claim that Black males are burdened more than Black females. Without attention to intersectionality, Black male achievement programs risk obscuring Black females and advancing patriarchal values. Black male achievement programs also risk reinforcing stereotypes that African American males are violent and dangerous. An intersectional approach would create space for Black male focused interventions, but require parity for Black female programs.